Happiness, Love, and Friendship as Grotesque Imagery in Oscar Wilde’s Fairy-Tales: Bakhtinian Perspective - Naufaludin Anam; Nurfathi Robi (Journal of Language and Literature, 2025)
Grotesque is an image or aesthetic form that presents a nuance of bizarre and peculiar. Commonly understood, that grotesque may posits negative connotation and horrible forms of symbol lies in works of arts, architecture, and even in literary works. Within literary works grotesque imagery may posit certain interpretation and value, depends on the lied perspective to see. Here in this research, researchers put a lens through children’s literatures or fairy-tales to investigate the images of grotesque which may indicating certain value. Three selected Oscar Wilde fairy tales were chosen as material objects in this research. Investigation of grotesque imagery is conducted by comprehensive reading and content analysis to elaborate the findings. Bakhtin theory of grotesque is applied as theoretical framework of analysis. Then, hermeneutical analysis is applied to interpret the image and elaboration of the meaning with the Bakhtinian notion of grotesque imagery and body. Result of the research indicated that there are some grotesque images represented in Wilde’s fairy tales with distinctive depictions: a) materialist construction of body and willingness to sacrifice for others happiness; b) degrading value of love as materialist and void sacrificial act; c) grotesque subject for friendly relationship and death for blossoms rebirth. This provides some evidence how grotesque aesthetics became Wilde's ways to depict how easily human’s grandiose conception substituted or represented by shallow and trivial objects. Furthermore, as demonstrated by this research findings, Wilde use grotesque imagery to evoke more radical issue like “materialism”, “self-sacrifice”, “death”, and “unusual love or relationship”.